Oil Palm Empty Fruit Bunch Fibre (OPEFB) in thermosetting polymer composite / Ahmad Afham Che Mohd Ruzaidi and Normila Ahmad - Che Mohd Ruzaidi, Ahmad Afham; Ahmad, Normila (2023)
The studies of characteristics in natural fibres have been intensified in recent decades. However, the application of its use is still not widespread. Due to the issue of environmental conditions being increasingly affected by carbon dioxide (CO₂) emissions, significant changes in climate and weather patterns are also observed. This research offers a new idea that can be commercialised, taking substantial steps in introducing natural fibre-reinforced polymer composite (NFRPC) products. This especially pertains to the distinctive characteristic of OPEFB in the construction industry market.